1984
DOI: 10.1111/j.1540-6261.1984.tb04923.x
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Minimizing Strategy for Portfolio Immunization

Abstract: Consider a fixed‐income portfolio whose duration is equal to the length of a given investment horizon. It is shown that there is a lower limit on the change in the end‐of‐horizon value of the portfolio resulting from any given change in the structure of interest rates. This lower limit is the product of two terms, of which one is a function of the interest rate change only, and the other depends only on the structure of the portfolio. Consequently, this second term provides a measure of immunization risk. If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…D uration is a subject of much concern to researchers and bond portfolio managers. In the last five decades, the literature on duration has grown from a simple explication of its property as a measure of average maturity (Macaulay (1938)) to sophisticated strategies such as funding multiple liabilities (Fong and Vasicek (1984)). Duration, however, is not without its critics.…”
mentioning
confidence: 99%
“…D uration is a subject of much concern to researchers and bond portfolio managers. In the last five decades, the literature on duration has grown from a simple explication of its property as a measure of average maturity (Macaulay (1938)) to sophisticated strategies such as funding multiple liabilities (Fong and Vasicek (1984)). Duration, however, is not without its critics.…”
mentioning
confidence: 99%
“…Bierwag, Kaufman, and Toevs (1983) further suggested that a hybrid of immunisation and active strategies could produce a strategy that guarantees a minimum return, but allow for the possibility of higher returns, known as contingent immunisation (Bierwag, et al, 1983). Fong and Vasicek (1984) expressed concern that the portfolio would not be immunised unless interest rate changes actually conformed to the predicted stochastic process. To overcome this, a bond portfolio was established and the exposure of interest rate changes to each portfolio characteristic determined.…”
Section: Literature Reviewmentioning
confidence: 98%
“…By minimising these risk measures, a portfolio could be structured in such a way as to have as little exposure to interest rate fluctuations as possible. At the time, Fong and Vasicek said, "[T]his is indeed the perfectly immunised portfolio, since no interest rate change affects its end-ofhorizon value" (Fong & Vasicek, 1984, p. 1543. Shiu (1987) repeated Fisher and Weil's (1971) immunisation tests and found that the durationbased immunisation did not work nearly as well as originally reported.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…An early strand of literature, referred to as functional immunization, assigned speci c functional forms to any admissible term structure updating (e.g., parallel shifts in Fisher and Weil (1972), arbitrary variations in Fong and Vasi cek (1984), and selected analytical forms in Chambers and Carleton (1988), Prisman and Shores (1988), Barrett et al (1995), Phoa andShearer (1997), andRodrigues De Almeida et al (1998)) and provided selection criteria for bond portfolios to make them nancially insensitive to these deformations. The approach exhibits the remarkable feature of accounting for full information about the crosssection.…”
Section: Introductionmentioning
confidence: 99%